Etika Sosial Dalam Agama Islam Dan Buddha - Cahya Kusuma; Doni Putra (Jurnal Budi Pekerti Agama Buddha, 2023)
According to Permendiknas No. 58 of 2009 early childhood education is a form of education that focuses on laying the foundation for growth and 5 developments, namely: moral and religious development, physical development (fine and gross motor coordination), intelligence/cognitive (thinking power, creativity) ), socio-emotional (attitudes and emotions and communication, in accordance with the uniqueness and stages of development according to the age group passed by early childhood). In the law of the Republic of Indonesia no. 20 of 2003 concerning the National Education System, especially the seventh part of the article 28 paragraph 1) Early Childhood Education is held before Basic Education and paragraph 2) Early Childhood Education can be provided through formal, non-formal and/or informal education. From the provisions of the law of the Republic of Indonesia or the provisions of the Minister of National Education that Early Childhood Education is important.